Utilizing XFEM model to predict the flexural strength of woven fabric Kenaf FRP plate strengthened on plain concrete beam - Omar, Zaim; Sugiman, Sugiman; Mansor, Hazrina; Ahmad, Hilton (Elsevier, 2023)
The evolution of advancing computing technology has encouraged the use of finite element analysis to require constitutive models, mostly adopted extensive experimental datasets. Never¬theless, fewer material properties are required within the bilinear traction-separation relationship incorporated with the XFEM technique and require fewer computation efforts due to the energetic approach simulation. This study used ABAQUS CAE 2021 to predict the flexural strength of plain concrete beams strengthened with Kenaf Fibre Reinforced Polymer (KFRP) plates under a four-point bending test, later validated with experimental datasets. The varying parameters, including woven fabric architectures, lengths, widths, and plate thickness, were considered. The results demonstrated that the consistency proposed modelling technique in this study well-captured failure modes and crack development as experimental observations. All models demonstrated an increase in peak load, and a comparison of load-deflection profiles was made between the numerical FEA modelling with the experimental works. The peak load discrepancies between the numerical outputs and the experimental datasets were found to be less than 12% in all testing series. Despite promising findings, stress analysis on peel and shear stresses associated with failure modes exhibited was performed. It was found that KFRP ruptures occurred due to peel stress peak at plate mid-span, while shear mode failure demonstrates concentrated peel stress (to lesser extent shear stress) at KFRP edge tip. Hence, a more unified approach is promoted to require only two material properties (preferably independently measured values). This approach enables a designer to choose the optimum FRPs size using the current modelling tool, substan¬tially reducing laborious and expensive experimental setup.